Role of Pain-Based Catastrophizing in Pain, Disability, Distress, and Suicidal Ideation. Issue 2 (3rd April 2017) - Noyman-Veksler, Gal; Lerman, Sheera F.; Joiner, Thomas E.; Brill, Silviu; Rudich, Zvia; Shalev, Hadar; Shahar, Golan
Abstract : Background : In chronic pain, patients' coping affects their adaptation. In two studies, we examined the role of pain catastrophizing, a maladaptive coping strategy, in pain, distress, and disability. In Study 2 we compared catastrophizing to pain acceptance and to other coping strategies. Methods : Study 1 . Chronic pain patients ( N = 428) were assessed four times as to their pain, disability, catastrophizing, and distress (depression and anxiety). Study 2 . Patients ( N = 165) were assessed as to coping and pain acceptance, pain, related distress, depression, hope, suicidal ideations, perceived burdensomeness, and thwarted belongingness. Results : Study 1 . A Structural Equation Modeling (SEM) analysis revealed that Time 1 Pain-based catastrophizing prospectively predicted pain (β =.36, p < .001). Distress prospectively predicted pain related disability (β = .34, p <.001). Study 2 . Pain-based catastrophizing predicted sensory pain (β = .22, p = .018), depression (β = .43, p < .001), and suicidal ideation ( O.R. = 1.88), which were also predicted by depression and perceived burdensomeness. Distraction predicted sensory pain (β = .21, p = .017, respectively). Activity engagement predicted low levels of depression (β = -.29, p < .001, respectively), and willingness to accept pain predicted low pain-related distress (β = -.16, p = .05). Conclusions : Pain catastro-phizing and pain acceptance constitute risk and resilience factors. Both should be assessed and targeted in pain management.